2014
DOI: 10.1002/cbdv.201200173
|View full text |Cite
|
Sign up to set email alerts
|

Quinone Derivatives from the Genus Rubia and Their Bioactivities

Abstract: The extracts and phytochemicals of the genus Rubia have drawn much attention due to their potent effects; among them, naphthoquinone and cyclopeptide derivatives, with significant biological activities, have great potential to be developed to new drugs. This review updates and compiles a total of 142 quinone derivatives including anthraquinone and naphthoquinone derivatives, occuring in twelve Rubia species. These compounds were listed together with their sources, melting points, bioactivities, as well as 112 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…Anthraquinones and derivatives are present in various plant roots. For example, a review by Xu et al [ 1 ], which includes a discussion of structure-activity relationships, lists 142 quinone derivatives in 12 Rubia species. Zengin et al [ 2 ] showed that Asphodeline roots might provide a new source of bioactive quinones and other natural compounds, and Usai and Marchetti [ 3 ] describe the distribution of anthraquinones in the Rubia peregrina L. plant.…”
Section: Introductionmentioning
confidence: 99%
“…Anthraquinones and derivatives are present in various plant roots. For example, a review by Xu et al [ 1 ], which includes a discussion of structure-activity relationships, lists 142 quinone derivatives in 12 Rubia species. Zengin et al [ 2 ] showed that Asphodeline roots might provide a new source of bioactive quinones and other natural compounds, and Usai and Marchetti [ 3 ] describe the distribution of anthraquinones in the Rubia peregrina L. plant.…”
Section: Introductionmentioning
confidence: 99%
“…Rubia species being one of the earliest plant resources possessed important commercial and medicinal values. Commercially, they were used as natural dye-stuffs in old days and improved commodity circulation; medically, these species being used as drugs were first recorded in the world famous pharmacy book of China, Divine Famer ' s Materia Medica , which has over 2000 years history [2]. According to many medical books, the roots of Rubia plants being reputed for their satisfactory efficacy were wildly used for the treatment of cancers, tuberculosis, rheumatism, hematemesis, metrorrhagia, epistaxis, contusion and menoxenia in the Chinese traditional medicine [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Several of the most widely distributed quinones and naphthoquinones are reported to possess a variety of pharmacological properties, including anti-inflammatory, antifertility, leishmanicidal, antibacterial, antifungal, hypolipidemic, antiatherosclerotic, and antimalarial effects (Thomson 1971;Qiu et al 1998;Kayembe et al 2010;Tandon and Kumar 2013;Xu et al 2014).…”
Section: Introductionmentioning
confidence: 99%